Blown Away in the Wind of Change: Can Extinct School Folktales be awakened through Mathematics Storytelling in Nigerian Basic Education? - Abah, Joshua Abah; Iji, Clement Onwu; Abakpa, Benjamin Ogbole (International Journal on Emerging Mathematics Education, 2018)
Storytelling has been severally regarded as the oldest method of instruction delivery, particularly for children. This study adopts a simple survey research design to explore the extent of storytelling usage by teachers in the mathematics classroom at the primary education level in Nigeria. The investigation was conducted on the premise that traditional folktales are heading down the path to extinction and are steadily being blown away in the wind of change being fanned by increasing technology penetration in the country. The participants of the study are 38 mathematics teachers drawn randomly from primary schools within Makurdi metropolis of Benue State, Nigeria. Analysis of data obtained through the Basic mathematics Storytelling Investigation (BMSI) revealed that despite the high level of awareness of storytelling as a teaching approach among mathematics teachers, only a meager 37% make use of stories in their mathematics classroom. Additional thematic analysis of stories described by the teachers showed that stories were used to illustrate learning points and motivate learners to action within the instructional context. An unintended outcome from the qualitative methods unveiled specific patterns of stories used by the mathematics teachers that are far from local folktales and oral traditions. There was also an indication that with an appropriate awareness campaign, primary mathematics teachers intend to use storytelling in their future teaching practice.